Miguel Street: A Microcosm of Cultural Conflicts in Postcolonial Trinidad - Mrs. Manju Singh; Prof. Mamta Singhal (International Journal of Scientific Research in Humanities and Social Sciences, 2025)
‘Cultural Conflicts’ is the most dominant concept used in contemporary discourse about society. The concept is used in different ways. It refers to pattern of beliefs and values, reflected in behaviour and institution passed on generation to generations. The storylines in the novels talk about people from various cultures and locations coming together for a definite cause. Cultural conflict arises as a result of their travel from one state to another with diversity of cultures. Their migration creates upheaval in their life. They experience cultural tension. They do not adhere to the norms and concerns of their indigenous culture. They lose their cultural identity. They become powerless while pursuing their own culture at the location of their choice. They adopt the culture of the other place as their main culture. As a result, the characters in the selected novels have different ways of life.